Resistive switching characteristics of mixed oxides. Issue 1 (1st June 2015) - Misra, Pankaj; Katiyar, Ram Sharan; Khurana, Geetika; Sharma, Yogesh
Abstract : The unipolar resistive switching (RS) properties of amorphous lanthanum gadolinium oxide (LaGdO3 ) and samarium gadolinium oxide (SmGdO3 ) thin films deposited by pulsed laser deposition on platinised silicon substrate with platinum top electrode have been investigated. Reliable and repeatable non-volatile switching of the resistance of these materials was obtained with sufficiently large resistance ratio and non-overlapping and low switching voltages. In the case of SmGdO3, a multilevel RS with four resistance states was observed by controlling the compliance current that opens the possibility of multi-bit storage. The switching between low- and high-resistance states was attributed to the formation and rupture of conductive filaments, while multilevel switching was attributed to the variation in diameter of conducting filaments with changing compliance current. On the other hand, forming free bipolar resistive switching behaviour was found in graphene oxide (GO) thin films on indium tin oxide (ITO) substrate with platinum as the top electrode. The switching between the low-resistance state and high-resistance state showed a reliable and repeating behaviour with an on/off ratio of 10 4 at room temperature. The device showed good endurance and retention characteristics. The switching mechanism was found to be governed by the migration of oxygen between the GO layer and bottom ITO electrode.